PSMA-Targeting Reduction-Cleavable Hyperbranched Polyamide-Amine Gene Delivery System to Treat the Bone Metastases of Prostate Cancer - Ye Y (Dove Medical Press, 2020)
Yongheng Ye1 ,* Lingli Zhang2 ,* Yuhu Dai,1 Zhi Wang,3 Cuie Li,3 Yue Peng,4 Dong Ma,2 Peiheng He1 1Department of Orthopedic Surgery, Guangdong Provincial Key Laboratory of Orthopaedics and Traumatology, The First Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangzhou, Guangdong Province 510080, People’s Republic of China; 2Key Laboratory of Biomaterials of Guangdong Higher Education Institutes, Department of Biomedical Engineering, Jinan University, Guangzhou 510632, People’s Republic of China; 3Guangzhou Institute of Biomedicine and Health, Chinese Academy of Sciences, Guangzhou, Guangdong Province 510530, People’s Republic of China; 4Department of Otorhinolaryngology Head and Neck Surgery, Zhuhai People’s Hospital (Zhuhai Hospital Affiliated with Jinan University), Zhuhai, Guangdong Province 519000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Peiheng HeDepartment of Orthopedic Surgery, Guangdong Prov Key Laboratory Orthopaed & Traumatol, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, Guangdong Province 510080, People’s Republic of ChinaEmail hepeiheng@mail.sysu.edu.cnDong MaKey Laboratory of Biomaterials of Guangdong Higher Education Institutes, Department of Biomedical Engineering, Jinan University, Guangzhou 510632, People’s Republic of ChinaEmail tmadong@jnu.edu.cnObjective: This study aimed to develop aptamer-anchored hyperbranched poly(amido amine) (HPAA) for the systemic delivery of miRNA-133a-3p and to evaluate its therapeutic potential against bone metastasis of prostate cancer in vivo and in vitro.Methods: A glutathione (GSH)-responsive cationic HPAA was prepared by the Michael addition reaction. Furthermore, HPAA-PEG was produced by PEGylation, and then the aptamer targeted to prostate-specific membrane antigen (PSMA) was conjugated to the HPAA-PEG. The obtained HPAA-PEG-APT could form nanocomplexes with miRNA-133a-3p through electrostatic adsorption.Results: The results of immunocytochemistry indicated that the complexes could target PSMA-expressing LNCaP cells. The ability of HPAA-PEG-APT to facilitate the delivery of miRNA-133a-3p into LNCaP cells was proven, and HPAA-PEG-APT/miRNA-133a-3p demonstrated enhanced antitumor activity, lower cytotoxicity and better biocompatibility in vitro. Moreover, in a mouse tibial injection tumor model, the intravenous injection of the HPAA-PEG-APT/miRNA-133a-3p complex significantly inhibited cancer growth and extended the survival time.Conclusion: This study provided an aptamer-anchored HPAA-loaded gene system to deliver miRNA-133a-3p for better therapeutic efficacy of bone metastasis of prostate cancer.Keywords: miRNA, aptamer, hyperbranched polyamide amine, bone metastasis, prostate cancer